Cost‐Effectiveness of Risk Score–Stratified Hepatocellular Carcinoma Screening in Patients with Cirrhosis. Issue 6 (June 2017) - Goossens, Nicolas; Singal, Amit G; King, Lindsay Y; Andersson, Karin L; Fuchs, Bryan C; Besa, Cecilia; Taouli, Bachir; Chung, Raymond T; Hoshida, Yujin
Abstract : OBJECTIVES: : Hepatocellular carcinoma (HCC) surveillance with biannual ultrasound is currently recommended for all patients with cirrhosis. However, clinical implementation of this "one‐size‐fits‐all" approach is challenging as evidenced by its low application rate. We aimed to evaluate the cost‐effectiveness of risk‐stratified HCC surveillance strategies in patients with cirrhosis. METHODS: : A Markov decision‐analytic modeling was performed to simulate a cohort of 50‐year‐old subjects with compensated cirrhosis. Risk‐stratified HCC surveillance strategies was implemented, in which patients were stratified into high‐, intermediate‐, or low‐risk groups by HCC risk biomarker–based scores and assigned to surveillance modalities tailored to HCC risk (2 non‐risk‐stratified and 14 risk‐stratified strategies) and compared with non‐stratified biannual ultrasound. RESULTS: : Quality‐adjusted life expectancy gains for biannual ultrasound in all patients and risk‐stratified strategies compared with no surveillance were 1.3 and 0.9–2.1 years, respectively. Compared with the current standard of biannual ultrasound in all cirrhosis patients, risk‐stratified strategies applying magnetic resonance imaging (MRI) and/or ultrasound only in high‐ and intermediate‐risk patients, without screening in low‐risk patients, were cost‐effective. Abbreviated MRI (AMRI) for high‐ and intermediate‐risk patients had the lowest incremental cost‐effectiveness ratio (ICER) of $2, 100 per quality‐adjusted life year gained. AMRI in intermediate‐ and high‐risk patients had ICERs <$3, 000 across a wide range of HCC incidences. CONCLUSIONS: : Risk‐stratified HCC surveillance strategies targeting high‐ and intermediate‐risk patients with cirrhosis are cost‐effective and outperform the currently recommended non‐stratified biannual ultrasound in all patients with cirrhosis.